Philippine history. ([Place of publication not identifed] : [publisher not identified])
This book presents the social, political, and economic history of the Filipino people. It aims to serve as an adequate basic textbook on Philippine history for the secondary schools in the Philippines.
Unit I : Introduction -- I. Introduction -- Unit II : Our country and people -- II. Physical features of the Philippines -- III. The Birth of the Filipino people -- Unit III : Our cultural development and progress -- IV. Stages of our cultural development -- V. Characteristics of the culture of the early Filipinos -- VI. Our social and religious progress -- VII. Our educational progress -- Unit V. Our economic development and progress -- VIII. Our agricultural development and progress -- IX. Our progress in commerce and trade -- Unit V : Discovery and conquest of the Philippines -- XI. The discovery of the Philippines -- XII. Explorations, conquest, pacification -- XIII. Defending and extending the colony
Includes bibliographical references and index.
Keywords: PHILIPPINES -- HISTORY